Anti HIV-1 and antimicrobial activity of the leaf extracts of Calotropis procera - Mohanraj, Remya; Rakshit, Jyotirmoy; Nobre, Malcolm (International journal of green pharmacy, 2010)
Calotropis procera R.Br. (Asclepiadiaceae) is an important medicinal plant whose leaves and roots have multiple uses. The plant is a rich source of many bioactive compounds which are of medicinal importance. The study was undertaken to investigate the anti HIV-1 and antibacterial activities of the crude leaf extracts of C. procera. Hot water extract was used for evaluating the efficacy against the growth of HIV. Inhibition of p24 antigen's expression was used as the method for the study. Antibacterial activity was tested against four different bacteria using agar well diffusion method. Zones of inhibition were measured with different concentrations of the extracts and some of them gave better values than the antibiotics used. The results were presented as the average and standard error of triplicate experiments. The statistical significance was checked at P<0.5. A dose-dependent inhibition of the p24 antigen expression was observed and the extract was found to be efficient against HIV-1. Ethyl acetate extract was effective against all the bacteria tested. The results observed support ancient and traditional medicinal values of C. procera.